2010
DOI: 10.1159/000320548
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inactivation of Cardiac 14-3-3 Protein <i>in vivo</i> Elicits Endoplasmic Reticulum Stress (ERS) and Activates ERS-initiated Apoptosis in ERS-induced Mice

Abstract: Background/Aims: Excessive endoplasmic reticulum stress (ERS) triggers apoptosis in various conditions including diabetic cardiomyopathy and pressure overload-induced cardiac hypertrophy and heart failure. The primary function of 14-3-3 protein is to inhibit apoptosis, but the roles of this protein in protecting against cardiac ERS and apoptosis are largely unknown. Methods: We investigated the roles of 14-3-3 protein in vivo during cardiac ERS and apoptosis induced by pressure overload or thapsigargin injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…In this study, we performed ascending AB surgery since this technique provides a more direct and rapid source of pressure overload on the LV together with a significant degree of hypertrophy after 48 hours [15,16]. We have shown that seven days pressure overload induced by AB surgery resulted in similar increases in the HW/BW ratio, cardiomyocyte diameter, and the expression levels of cardiac ANP and galectin-3 in the WT and DN p38 mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we performed ascending AB surgery since this technique provides a more direct and rapid source of pressure overload on the LV together with a significant degree of hypertrophy after 48 hours [15,16]. We have shown that seven days pressure overload induced by AB surgery resulted in similar increases in the HW/BW ratio, cardiomyocyte diameter, and the expression levels of cardiac ANP and galectin-3 in the WT and DN p38 mice.…”
Section: Discussionmentioning
confidence: 97%
“…To induce pressure overload in the mice, we performed ascending AB surgery, since this technique provides a more direct and rapid source of pressure overload on the left ventricle (LV) with a significant degree of hypertrophy after 48 hours [15,16]. Ten-to twelve-week-old male WT (WT AB; n = 6) and DN p38 MAPK mice (DN p38 AB; n = 7) were anesthetized intraperitoneally with Nembutal 50 mg/kg body weight.…”
Section: Ascending Aortic Banding (Ab) Surgerymentioning
confidence: 99%
“…Phosphorylations at S43, S233, and S259 sterically inhibit Raf-1 binding to GTP-Ras and promote, instead, binding to the adapter/chaperone protein 14-3-3 (named for the separation fraction where it was discovered). Various 14-3-3 isoforms often hold proinflammatory client proteins like Raf1 inactive in the cytoplasm as shown in FIGURE 3 (1537,2103,2125). There is a suggestion that upregulation of 14-3-3 proteins may be protective in atherosclerosis, although assignment of specific roles for the different isoforms is difficult (218,1052).…”
Section: Activation Of Raf1 a Prototypical Map3k And Other Activatomentioning
confidence: 99%
“…Cardiac specific expression of a dominate negative-14–3–3 protein in mice increased apoptotic cell death under stress such as cardiac hypertrophy, diabetic cardiomyopathy, and heart failure, suggesting that 14–3–3 proteins are essential for cardioprotection during stress to the heart [40]. …”
Section: Resultsmentioning
confidence: 99%